Mobile application For Locating Buses at the University Park - CHONGARA Haitham Mr. SOLTANI Khaled ● MERAGHNI Laid ● LARROUM Oualid (university of eloued جامعة الوادي, 2022)
The objective of this project is to implement a mobile application that allows to determine the bus location in the park of the university . The location of the bus can be determined by a ” Map ” on which the location of the bus is indicated . This application helps to solve the search process and determine the bus locationL’objectif de ce projet est de mettre en oeuvre une application mobile qui permet de d´eterminer l’emplacement de la bus dans le parc de l’universit´e . L’emplacement de la bus peut ˆetre d´etermin´e par ” Google Maps ” sur laquelle l’emplacement de l’autobus est indiqu´e . Cette application aide `a r´esoudre le processus de recherche et `a d´eterminer l’emplacement du bus
licence mémoire informatique
Keywords: Bus - Mobile Application - Database; Bus - Application Mobile - Base de Don´ees